The Challenging conversation: Peace culture regarding Costa Rican sexual education - Mézerville López, Claire Marie (2018)
This article presents a reflexion about the impact of identity politics regarding the polarizing discourses about sexual education in Costa Rican public education. It also refers to the difuse conceptualization of the so called “gender ideology” and the concerns it raises from the comunity. An integrating proposal about the necesary principles for healthy sexual education is presented, which was ratified by ten costa rican psychologist, including the author. A peace culture that builds on engaging all parties, as well as the capacity to open safe spaces for dialogue are fundamental to face the delicate issues that involve Costa Rican underage population.